ANALYSIS OF COMMUNICATIVE STRATEGY OF NGO OF THE CHARITABLE ORIENTATIONAL - N. Bezverbnaya (Вестник университета)
In article the communication channels promoting implementation of charitable and socially important projects for non-profit organizations of a charitable orientation are investigated. Need of maintenance of communication with donors, investors by volunteers is proved. Not only ways of communication and attraction of donations, but also actions which will be able to hold the donor are investigated.